P.044 GMPPB mutation causes a muscular dystrophy-myasthenic spectrum. (June 2022) - Beland, B; Jewett, G; Khayambashi, S; Chhibber, S
Abstract : Background: Mutations in GDP-Mannose Pyrophosphorylase B (GMPPB) cause a spectrum of disease ranging from muscular dystrophy to congenital myasthenic syndrome (CMS). Recognition of neuromuscular junction dysfunction has important treatment implications. Methods: We describe a person with GMPPB mutation causing an overlapping limb girdle muscular dystrophy - myasthenic syndrome with robust response to acetylcholinesterase inhibitors. We review the literature on the muscular dystrophy - CMS and explore the phenotypic features that aid in recognizing neuromuscular junction dysfunction. Results: A 35-year-old woman presented with a 10-year history of debilitating myalgias, symmetrical limb girdle and neck weakness, and chronic CK elevation. Electromyography showed a non-irritable myopathy. Biopsies were consistent with muscular dystrophy. Whole genome sequencing revealed two heterozygous pathogenic mutations in the GMPPB gene, giving a diagnosis of genetically confirmed limb girdle muscular dystrophy. Subsequently, repetitive nerve stimulation revealed decrement in the trapezius muscle suggestive of an overlap myasthenic syndrome. She was started on pyridostigmine resulting in recovery of full motor power with significant functional improvement. Conclusions: Identification and treatment of neuromuscular junction dysfunction caused by GMPPB mutations can significantly improve motor power and function. Early onset of progressive fatigable proximal weakness, spared ocular and facial muscles, and pyridostigmine responsiveness are important features of GMPPB-related CMS.